Geoheritage assessment, protection, and management - Reynard, Emmanuel; Brilha, José (Elsevier, 2018)
For the last 20 years there has been a growing interest in the geosciences for topics related to geoheritage: geoconservation, geotourism and geoparks. Geoheritage: Assessment, Protection, and Management is the first and only reference book to cover these main topics as well as the relationship of geoheritage to other subjects such as landscapes, conservation, and tourism. The book also includes methodologies for assessment, mapping, and visualisation, along with case studies and colour images of some of the most important global geosites. This book is an essential resource for geoscientists, park and geopark managers, tourism and regional planning managers, as well as university students interested in geoheritage, geosites, geomorphosites, geoconservation, and geotourism. It also includes critical information on UNESCO’s Global Geoparks, World Heritage and Biosphere Reserve sites, national parks and protected areas in general, land-use planning and nature conservation policies, and in the general contribution of geodiversity for sustainable development.--Provided by publisher.